PERCEPTION OF MILLENNIAL TOURISTS TOWARD FACILITIES AND SERVICES AT JAKARTA NATIONAL MUSEUM - Putu Gde Arie Yudhistira (Pusat penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2018)
The Jakarta National Museum is the first and largest museum in Jakarta and it is the largest in Southeast Asia. The study aimed to analyze and describe how millennial tourists perceived before visiting the facilities and services at the Jakarta National Museum. In the millennial era, millennial tourists currently become one of the tourists who like practical things and want to know new things and this can be found at Jakarta's national museum. The method used in this study was qualitative by linking three variables, namely the perception before visiting tourists, expectations and perceptions of the objects’ quality. Data collection techniques used interviews. The data analysis process carried out data collection (interviews, observations, documents) then data reduction, coding according to parameters and indicators and interpretation. The validity test of this research was carried out using source triangulation. The results of this study indicated that the perception of millennial tourists before visiting states that the National Museum held many historical relics and had good facilities. The motivation ofvisitors was for curiosity needs. The expectation was to expect the National Museum to be bigger than they imagined, hoping that the service at the National Museum would be better than other museums, has a very complete collection, the layout of the museum collection was neat and clean. While the perception after visiting the National Museum had a lot of heritage of Indonesian culture and history, it had excellent facilities, the order of historical objects neatly arranged and easy to see, had friendly and good staffs in communication. The National Museum was also comfortable, safe, clean and well-maintained. Thus the comparison of tourists' perceptions and expectations before and after the visit is appropriate and it even exceeds expectations.